Proyek Pembuatan Candi dari Kertas Lipat sebagai Media Pembelajaran Science, Technology, Engineering, Arts and Mathematics (STEAM) di Sekolah Dasar - Hardani Hardani; Imam Fitri Rahmadi; Farida Nurhasanah (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2022)
The development of science, technology, and art requires learning innovations in elementary schools that are more connected to the real world and able to hone 21st century learning skills. One of the innovations that can be done is to introduce new media and approaches for students to learn in a more integrated manner through learning STEAM based. The purpose of this research; 1) evaluate students' experiences in learning using the STEAM approach by building temples out of folded paper; 2) observing students' activities in learning using the STEAM approach by building temples from folding paper related to 21st century learning skills; and 3) reviewing the relationship between the activities of building temples out of folded paper and the STEAM discipline. This research is an exploratory study using a qualitative approach combined with the Engineering Design Process (EDP) which was attended by 25 elementary school students. The results showed that students had a pleasant experience from the activity of making temples using folded paper, the activity of making temples encouraged students especially to express creativity and critical thinking, and the activity of making temples seemed to have a relationship with all STEAM disciplines. Making temples from folding paper as a medium for STEAM learning can be adapted and continuously improved by using digital technology so that students can more dynamically compose and explore the shape of the temple.